The impact of coronary sinus narrowing on diastolic function in patients with refractory angina. (15th September 2019) - Szekely, Yishay; Topilsky, Yan; Bazan, Samuel; Revivo, Miri; Banai, Shmuel; Konigstein, Maayan
Abstract: Objective: Evaluating the impact of Coronary sinus (CS) narrowing on diastolic function. Background: Narrowing of the CS is an emerging therapy for refractory angina pectoris, improving perfusion to the ischemic subendocardium and relieving ischemia and angina. It was speculated that increased CS pressure might cause interstitial myocardial edema and diastolic dysfunction. Methods: Prospective assessment of diastolic function was performed at baseline and 6 months following CS Reducer implantation in consecutive patients treated for refractory angina. Diastolic function assessment included left atrial volume, early transmitral filling peak velocity (E wave), E wave deceleration time (DT), transmitral atrial wave velocity (A wave), and early diastolic velocity of the septal (e′ septal) and lateral (e′ lateral) aspects of the mitral annulus. Results: Twenty-four patients with chronic refractory angina and proven myocardial ischemia (mean age 69.3 ± 10.9 years) were included in the analysis. A wave velocity, E/A ratio, E wave DT and left atrial volume did not significantly change 6 months following Reducer implantation ( p  > 0.1 for all comparisons). A non-significant decrease in E wave velocity (80.5 ± 22.3 cm/s vs. 75.7 ± 17.5 cm/s, p  = 0.19) and non significant increase in e′ septal and lateral (5.28 ± 1.54 cm/s vs. 5.30 ± 1.71 cm/s, p  = 0.95 and 8.26 ± 1.85 cm/s vs. 8.46 ± 2.07 cm/s, p  = 0.69, respectively) led to a non-significant decrease in E/e′ average ratio (12.6 ± 5.7 vs. 11.4 ± 3.3, p  = 0.24). Mean diastolic function class significantly decreased following Reducer implantation from 1.5 ± 0.66 to 1.17 ± 0.76 ( p  = 0.008). Conclusion: Coronary sinus narrowing in patients with myocardial ischemia and refractory angina does not adversely affect diastolic function and may actually improve it. Highlights: Coronary sinus narrowing is an emerging therapy for refractory angina pectoris. This procedure was speculated to worsen diastolic dysfunction. Coronary sinus narrowing did not adversely affect diastolic function. Diastolic function may actually improve following coronary sinus narrowing.